Lakota america eaudiobook A new history of indigenous power. - Hamalainen, Pekka (Tantor Media, 2019)
The first comprehensive history of the Lakota Indians and their profound role in shaping America's history This first complete account of the Lakota Indians traces their rich and often surprising history from the early sixteenth to the early twenty-first century. Pekka Hämäläinen explores the Lakotas' roots as marginal hunter-gatherers and reveals how they reinvented themselves twice: first as a river people who dominated the Missouri Valley, America's great commercial artery, and then—in what was America's first sweeping westward expansion—as a horse people who ruled supreme on the vast high plains. The Lakotas are imprinted in American historical memory. Red Cloud, Crazy Horse, and Sitting Bull are iconic figures in the American imagination, but in this groundbreaking book they emerge as something different: the architects of Lakota America, an expansive and enduring Indigenous regime that commanded human fates in the North American interior for generations. Hämäläinen's deeply researched and engagingly written history places the Lakotas at the center of American history, and the results are revelatory.